E-INSPIRE- I. Bridging the gap with the local Universe: stellar population of a statistical sample of ultra-compact massive galaxies at z < 0.3 - Mills, John; Spiniello, Chiara; Sergeyev, Alexey; Tortora, Crescenzo; Khramtsov, Vladyslav; D'Ago, Giuseppe; Maksymowicz-Maciata, Michalina; Benedetti; Joao P.; V; Ferre-Mateu, Anna; Cappellari, Michele; et al. (OXFORD UNIV PRESS, 2025)
This paper presents the first effort to Extend the Investigation of Stellar Populations In RElics (E-INSPIRE). We present a catalogue of 430 spectroscopically confirmed ultra-compact massive galaxies (UCMGs) from the Sloan Digital Sky Survey at redshifts 0.01 < z < 0.3. This increases the original INSPIRE sample eightfold, bridging the gap with the local Universe. For each object, we compute integrated stellar velocity dispersion, age, metallicity, and [Mg/Fe] through spectroscopic stellar population analysis. We infer star formation histories (SFHs), metallicity evolution histories (MEHs) and compute the Degree of Relicness (DoR) of each object. The UCMGs, covering a wide range of DoR from 0.05 to 0.88, can be divided into three groups, according to how extreme their SFH was. The first group consists of 81 extreme relics (DoR greater than or similar to 6) that have formed the totality of their stellar mass by and have super-solar metallicities at all cosmic epochs. The second group (0.3 less than or similar to DoR less than or similar to 0.6) contains 293 objects also characterized by peaked SFHs but with a small percentage of later-formed stars and with a variety of MEHs. The third group (DoR less than or similar to 0.3), has 56 objects that cannot be considered relics since they have extended SFHs and formed a non-negligible fraction (> 25 per cent) of their stellar mass at . We conclude that the most efficient method of finding relics is to select UCMGs with a combination of large velocity dispersion values (as already found by INSPIRE), super-solar metallicities and high [Mg/Fe]